Sustainable Intensification of Livestock Production within MFS - Ahmed, S.; Miajy, Abdullah; Debnath, Manik; Cheesman, Stephanie; Bhandari, Humnath (International Rice Research Institute, 2023)
After crop production, livestock is one of the most important income generation sources for the village people, and 84% of village households in Bangladesh are involved with livestock production (animals or poultry or both). In Bangladesh, the livestock sector contributes about 2% of the national GDP. Despite the huge number of people involved with livestock production, the country suffers from an acute shortage of livestock products such as milk, meat, and eggs. In Bangladesh, the present milk, meat, and eggs production can meet only 50%, 87%, and 63% of the national demand.